Nicotinic Acetylcholine Receptor Signaling in Neuroprotection - Akaike, Akinori; Shimohama, Shun; Misu, Yoshimi (Springer Nature, 2018)
Alzheimer's disease; Neurodegenerative diseases; Nicotine; Transporter; Glia